Relations between cortical thickness, serotonin 1A receptor binding, and structural connectivity: A multimodal imaging study. Issue 2 (27th November 2017) - Pillai, Rajapillai L. I.; Malhotra, Ashwin; Rupert, Deborah D.; Wechsler, Bennett; Williams, John C.; Zhang, Mengru; Yang, Jie; Mann, J. John; Oquendo, Maria A.; Parsey, Ramin V.; DeLorenzo, Christine
Abstract: Serotonin 1A (5‐HT1A ) receptors play a direct role in neuronal development, cell proliferation, and dendritic branching. We hypothesized that variability in 5‐HT1A binding can affect cortical thickness, and may account for a subtype of major depressive disorder (MDD) in which both are altered. To evaluate this, we measured cortical thickness from structural magnetic resonance imaging (MRI) and 5‐HT1A binding by positron emission tomography (PET) in an exploratory study. To examine a range of 5‐HT1A binding and cortical thickness values, we recruited 25 healthy controls and 19 patients with MDD. We hypothesized increased 5‐HT1A binding in the raphe nucleus (RN) would be negatively associated with cortical thickness due to reduced serotonergic transmission. Contrary to our hypothesis, raphe 5‐HT1A binding was positively correlated with cortical thickness in right posterior cingulate cortex (PCC), a region implicated in the default mode network. Cortical thickness was also positively correlated with 5‐HT1A in each cortical region. We further hypothesized that the strength of 5‐HT1A ‐cortical thickness correlation depends on the number of axons between the raphe nucleus and each region. To explore this we related 5‐HT1A –cortical thickness correlation coefficients to the number of tracts connecting that region and the raphe, as measured by diffusion tensor imaging (DTI) in an independent sample. The 5‐HT1A –cortical thickness association correlated significantly with the number of tracts to each region, supporting our hypothesis. We posit a defect in the raphe may affect the PCC within the default mode network in MDD through serotonergic fibers, resulting in increased ruminative processing.